Lumbago in Adolescents Revealing Type 1 Neurofibromatosis About a Presentation (Global Journal of Medical Research, 2023)
Neurofibromatosis type 1 NF1 is an inherited disease caused by pathogenic variants of the NF1 gene present on chromosome 17 is an autosomal dominant disease of which occurs de novo The cardinal signs of NF1 are cafe-au-lait spots and cutaneous neurofibromas The ideal imaging is based on the realization of nuclear magnetic resonance imaging The treatment is based on the surgical removal of the tumor but report recurrence and malignant transformation that requires radiotherapy
Keywords: neurofibromatosis; lumbago